Ewolucja potencjału finansowego samorządu terytorialnego w Polsce w latach 1991-2004 - Miszczuk, Magdalena (Evolution of the Financial Potential of the Local Government in Poland between 1991 and 2004, 2007)
This article shows the evolution of the financial potential of the local government between 1999 and 2004. The study, which focused on its three tiers as well as the entire local government structure, was based on nominal and real income and expenditure of local government units and on change indicators. For a more comprehensive approach, local government income and expenditure were analyzed with respect to key public financial resources (the state budget and special purpose funds) as well as to the GDP. The results indicate an absolute increase in the financial potential of the local government and a simultaneous relative decrease in relation with other public funds and GDP during the last years under analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 478-487